Healthcare utilisation and unmet health needs in children with intellectual disability: a propensity score matching approach using longitudinal cohort data. Issue 5 (14th March 2022) - Nicholson, E.; Doherty, E.; Guerin, S.; Schreiber, J.; Barrett, M.; McAuliffe, E.
Abstract: Background: Health disparities for children with intellectual disabilities can be challenging to measure due to many other factors that can impact health and healthcare use. The aim of the current study was to use longitudinal cohort data to compare children with intellectual disability (ID) in Ireland between 2006 and 2014 on healthcare utilisation and unmet need, at ages 9 and 13, using a propensity score matching (PSM) approach. Methods: Using data from the Growing up in Ireland study, PSM was used to identify an appropriate control sample to compare with a sample of children with ID ( n = 124). Participants were matched on variables that are known to influence healthcare utilisation to reduce the impact of confounding variables between groups so that differences between the groups can be estimated. Logistic regression was used to estimate effects at ages 9 and 13. Results: Children with ID were no more likely to have visited a general practitioner or emergency department in the past 12 months than children without ID. They did have a greater likelihood of visiting a doctor in a hospital in the past 12 months and of having an overnight stay in hospital by age 9. Primary caregivers of children with ID were more likely to report unmet health needs at ages 9 and 13. Conclusions: This approach is a novel means of comparing healthcare use in this population by balancing the impact of other factors that may result in inequities, to which children with ID may be more vulnerable.